Six new species of the spider genus Centroctenus Mello-Leitão from the Neotropical region (Ctenidae, Cteninae) - Brescovit, Antonio D.; Torres, Richard A.; Rego, Felipe N. A. A.; Polotow, Daniele (Zootaxa, 2020)
The species of the genus Centroctenus can be distinguished from other Ctenidae genera by the presence of a long tibiae and the absence of a retrolateral projection of the cymbium in the male palp, and by the presence of a rounded spermathecae in the female epigynum. The composition of this spider genus is herein expanded to eleven Neotropical species, with the description of six new species: Centroctenus dourados sp. n., C. claudia sp. n., C. chalkidisi sp. n., and C. varzea sp. n., from Brazil; and Centroctenus coloso sp. n. from Colombia and Centroctenus alinahui sp. n. from Ecuador. A map with the distribution of all known species in the genus is presented.